The legal system for the authentication of the electronic signature - A comparative study - - Daza Yi, Azad Sadeeq Mohammed (Arab Journal for Sciences and Research Publishing, 2017)
The expansion of electronic commerce in the international community and its prosperity due to the ease of dealing and speed, but expansion accompanied by some cases of manipulation, forgery and penetration, especially with regard to electronic signature, so the laws of most countries of the world have a legal system to identify the signature by the third party. And to verify the data and information about the parties, so as to increase the confidence and security in the electronic signature to protect electronic business transactions, and the importance of documenting the electronic signature some laws were created in some countries to authorize authorities to authenticate granting special documentation certificate and identified documentation on the electronic signature measures to be more confident and secure, accurate and authoritative have a credible law.
Keywords: electronic signature; authentication bodies; authentication certificate; authentication procedures; electronic transactions